Asian Values, Authoritarianism and Capitalism in Singapore - Sim, Soek-Fang (Javnost-The Public, 2001)
This article takes issue with the widespread belief that capitalist development and material prosperity produce a middle class political culture that spells the end for dictatorial regimes and leads necessarily to liberal democracy. The case of Singapore, which is a very prosperous and highly developed capitalist economy with a large middle class, but whose government undoubtedly retains a strong authoritarian element, demonstrates that the link between capitalism and democracy is not at all automatic. The Progressive Action Party (PAP), which has since independence formed the government of Singapore, has successfully avoided the path to liberal democracy through its deployment of a discourse of "Asian Values" (AV). The article makes extensive use of the concept of hegemony, derived form the work of Antonio Gramsci. The PAP has secured its hegemony through the use of discourses of "Asian Capitalism" and "Asian Democracy." Because of their function in de-legitimising potential sources of counter-capitalistic contradictions and counter-authoritarian dissent, "Asian Values" enables the re-amalgamation, and even strengthens the mutual dependency, of authoritarianism and late-capitalism in Singapore. This article traces the evolution and inner structure of Asian Values discourses and uses the results of extensive fieldwork to demonstrate how this discourse has succeeded both in surviving the economic problems of the late 1990s and in marginalising alternative and oppositional opinions.